2017
DOI: 10.1103/physreve.95.052805
|View full text |Cite
|
Sign up to set email alerts
|

Contact angles of a drop pinned on an incline

Abstract: For a drop on an incline with small tilt angle α, when the contact line is a circle of radius r, we derive the relation mgsinα=γrπ/2(cosθ^{min}-cosθ^{max}) at first order in α, where θ^{min} and θ^{max} are the contact angles at the back and at the front, m is the mass of the drop and γ the surface tension of the liquid. We revisit in this way the Furmidge model for a large range of contact angles. We also derive the same relation at first order in the Bond number B=ρgR^{2}/γ, where R is the radius of the sphe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 30 publications
1
51
0
Order By: Relevance
“…The most effective hydrophobic surfaces found in nature are created using a microstructure, such as that in butterfly wings or the surfaces of lotus plants, and it has been shown that varying the microstructure of such a coating can modify the hydrophobicity of a surface, as well as the wetting properties [4][5][6]. The two extreme conditions for microstructure wetting are the Wenzel state, where the microstructure is filled with fluid, and the Cassie-Baxter state, where fluid is pinned on the entrance and exit corners of the microstructure [7][8][9]. Previous studies have shown that a microstructure comprised of spherical polytetrafluoroethylene (PTFE) nanoparticles is able to produce a superhydrophobic surface, with contact angles greater than 140 • [10,11] such as the surface shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The most effective hydrophobic surfaces found in nature are created using a microstructure, such as that in butterfly wings or the surfaces of lotus plants, and it has been shown that varying the microstructure of such a coating can modify the hydrophobicity of a surface, as well as the wetting properties [4][5][6]. The two extreme conditions for microstructure wetting are the Wenzel state, where the microstructure is filled with fluid, and the Cassie-Baxter state, where fluid is pinned on the entrance and exit corners of the microstructure [7][8][9]. Previous studies have shown that a microstructure comprised of spherical polytetrafluoroethylene (PTFE) nanoparticles is able to produce a superhydrophobic surface, with contact angles greater than 140 • [10,11] such as the surface shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…3, [28] Eq. 4 and [9] Eqs. 1 and 2), concluding to k varying in the range π/2 ≤ k ≤ 2, depending on the physical situation.…”
Section: Introductionmentioning
confidence: 99%
“…[1,3,5]), is that the shape of the footprint does not remain circular for α > 0. However, since most of the analytical approaches restrict to small values of α, those studies have considered a circular shape for the footprint [15,25]. Instead, we will extend now our previous theory in [27] for non-circular footprints on horizontal planes to inclined ones.…”
Section: Drop Shapementioning
confidence: 96%
“…The prediction for = 1 is compared with the small Bo theory developed by De Coninck et al [15], which is developed without the lubrication approximation. This solution for θ(ϕ) is written in the form…”
Section: A Contact Angle Distribution Along the Drop Peripherymentioning
confidence: 99%